Why is the smartphone market in Indonesia declining? - Siagian, Dergibson; Dema, Yosef (Jurnal Ekonomi Perusahaan, 2023)
Technology, particularly communication and information technology, is essential for everyone. As this technology advances, competition among cell phone manufacturers becomes more intense. This is the primary reason that mobile manufacturing companies compete to innovate in order to create mobile products that will catch the attention of market consumers. Cell phones appear to be a basic human requirement. But there is a new irony for Indonesia. Despite a 1.05% increase in population, the smartphone market in Indonesia fell by 11.9% in the first quarter of 2023 compared to the same quarter in 2022. The goal of this study is to determine which factors influence purchase intentions and which factors are the most likely cause of a decrease in purchasing intentions. The study's findings show that the four independent variables, product quality, brand image, brand prestige, and brand trust, all have a positive and significant effect on purchase intention. If there is a decrease in purchase intention, it is reasonable to suspect that the cause is the smallest value, which is far below the other three independent variables. Plagiarism Check